2020
DOI: 10.1590/s1677-5538.ibju.2020.s116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the sexual behavior of the population. The vision of the east and the west

Abstract: The COVID-19 pandemic has radically changed the way of life around the World. The state of alarm has forced the population to stay at home, radically changing both interpersonal and partner relationships; work at home, social distancing, the continued presence of children at home, fear of infection and not being able to physically meet with others have changed most people's sexual habits. We conducted a review by exploring the impact of the COVID-19 pandemic on sexual behavior in the population from three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
2
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(205 citation statements)
references
References 20 publications
9
175
2
19
Order By: Relevance
“…Governments of many countries ordered to close down gathering spaces and promote social distancing to prevent the spread of COVID-19. Not being able to physically meet with others may change people's sexual habits [14]. A social atmosphere of collective anxiety about the COVID-19 pandemic may also result in detriment of the mood to enjoy sex.…”
Section: Sex Life During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Governments of many countries ordered to close down gathering spaces and promote social distancing to prevent the spread of COVID-19. Not being able to physically meet with others may change people's sexual habits [14]. A social atmosphere of collective anxiety about the COVID-19 pandemic may also result in detriment of the mood to enjoy sex.…”
Section: Sex Life During the Covid-19 Pandemicmentioning
confidence: 99%
“…Leung et al reported that people with higher risk perceptions of severe acute respiratory syndrome (SARS) were more likely to take comprehensive precautionary measures against infection [19]. The fear of contagion itself may reduce physical contact within couples, from simple kissing to full sexual intercourse [14]. If the risk perception is excessive, particularly when a person is overwhelmed with negative SARS-related information, it will lead to irrational fear [20].…”
Section: Associations Of Risk Perception and General Anxiety With Chamentioning
confidence: 99%
“…11 Lockdown changed various factors that can affect sexual behavior, such as increase time available to partners, lack of privacy because of higher number of inmates at home, and stress arising out of economic shutdown and sudden change in interpersonal dynamics. 12 The major limitations of our study were the use of a convenient sampling, use of English media, using a cross-sectional design, and loss of sizable data because of incomplete responses (which could be because of sensitive nature of questions). Also, our study focused on the sexual behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Пандемия COVID-19 коренным образом изменила образ жизни во всем мире. Состояние тревоги заставило население оставаться дома, радикально изменив как межличностные, так и партнерские отношения; работа дома, социальное дистанцирование, постоянное присутствие детей дома, страх перед инфекцией и невозможность физически встречаться с другими людьми изменили сексуальные привычки большинства людей [19].…”
Section: конфликт интересовunclassified